Potencial eólico do estado da Bahia: oportunidades e entraves no seu aproveitamento para a produção de energia - VIANA, Anderson Souza (2014)
Wind power is considered a clean, renewable source, besides having less impact on the environment when compared with the impacts generated by the implementation of hydroelectric power plants, and the operation of the thermal. Brazil has established targets for increased production of energy from wind power. Considering the presented factors and environmental and socioeconomic benefits that are associated with the production of wind energy, it is necessary an analysis of the Bahian estimated wind potential of wind power by Atlas 2013, and the evolution of its use in the state of Bahia. This is the aim of this study: To analyze the progress of the use of wind power (onshore) of Bahia state for energy production, recently estimated by atlas published in 2013; discuss the positive and negative impacts associated with the production of wind energy in the state; and raise the possible consequences of the insertion in the energy matrix of the state. The state of Bahia has a pretty significant wind potential ships which generates a high possibility of expanding the use of this renewable energy source. Even with the great advance in the hiring of wind projects in recent auctions, the total power of the state in December 2013 is almost imperceptible before the full potential. However there must be a greater plan for the sector in order to avoid situations like that began in 2012 and extends for more than year, relating to wind farms in the region of Caetité, that even with the greatest potential installed on state proceeds with the contradiction of not generating power to the system due to lack of transmission lines. The environmental studies must contemplate all the factors related to short-and long-term enterprise. Avoiding a clean energy source can generate environmental impacts that are predictable and do not necessarily have a connection to your production system.